Estudo de isolados clínicos de Pseudomonas aeruginosa e Acinetobacter spp. multirresistentes do Hospital Universitário de Santa Maria - Santos, Silvana Oliveira dos (2014)
Pseudomonas aeruginosa and Acinetobacter spp. are non-fermenting Gram negative bacilli (NF-BGN), unable to use carbohydrates as an energy source through fermentation, are considered opportunistic and have great clinical importance in Related to Health Care Infections (HAIs). The high resistance to antimicrobials that these species present is attributed to a number of factors such as selective pressure of antimicrobials, inadequate empirical antimicrobial therapy, long periods of hospitalization and patient-related factors. A total of 102 isolates from the University Hospital of Santa Maria (HUSM) were studied with 63 Pseudomonas aerugionosa and 39 Acinetobacter spp.. The assessment of their sensitivity profile was performed using the standard disc diffusion method. Comparing the two genus, in this study, P. aeruginosa showed higher sensitivity than Acinetobacter spp. the antimicrobials tested. P. aeruginosa showed 85,7% sensitivity to polymyxin B and Acinetobacter spp. 41,0% to tetracycline.The mechanism of chromosome AmpC searched by the phenotypic test for beta-lactamase induction in Group 1 was only detected in P. aeruginosa (68,2%). None of the samples showed beta-lactamase extended spectrum (ESBL) evaluated the test of synergism or bringing the disks. Among P. aeruginosa, 57,1% were simultaneously sensitive to imipenem and meropenem, with these carbapenem-resistant strains were 100% sensitive to polymyxin B and tobramycin 61,5%. In the genus Acinetobacter only 15,4% were susceptible to imipenem and 17,9% to meropenem, but resistant to this class samples showed 100% sensitivity to polymyxin B and 59,4% to tetracycline. Multidrug resistance to antimicrobials detected this nosocomio mainly isolates of Acinetobacter spp. shows the importance of monitoring the sensitivity profile for the promotion of patient safety with the introduction of effective empiric treatment, and to constitute an attempt to minimize bacterial resistance.